2005
DOI: 10.1007/s10340-005-0113-6
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation pheromone traps, a major component of IPM strategy for the red palm weevil, Rhynchophorus ferrugineus in date palms (Coleoptera: Curculionidae)

Abstract: The population fluctuation of the red palm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 0 publications
4
55
0
1
Order By: Relevance
“…They reported that from an initial level of 4.12 weevils per trap per week in 1994, the adult population was reduced to 2.02 weevils per trap per week at the end of 1997. In United Arab Emirates, by using pheromone trapping in three date palm orchards during 2000 and 2001, the populations of RPW was reduced by 29.7-51.7% (Abbas et al 2002). In Abu Dhabi Emirate, it has been reported that about two million of red palm weevil adults were trapped during the first half of the year 2013 through a project implemented by Abu Dhabi Farmers' Services Centre (ADSFC) in coordination with Abu Dhabi Food Control Authority (ADFCA), that covers about 23,050 orchards, where about 118,797 pheromone traps have been installed in these orchards (Gulf News, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…They reported that from an initial level of 4.12 weevils per trap per week in 1994, the adult population was reduced to 2.02 weevils per trap per week at the end of 1997. In United Arab Emirates, by using pheromone trapping in three date palm orchards during 2000 and 2001, the populations of RPW was reduced by 29.7-51.7% (Abbas et al 2002). In Abu Dhabi Emirate, it has been reported that about two million of red palm weevil adults were trapped during the first half of the year 2013 through a project implemented by Abu Dhabi Farmers' Services Centre (ADSFC) in coordination with Abu Dhabi Food Control Authority (ADFCA), that covers about 23,050 orchards, where about 118,797 pheromone traps have been installed in these orchards (Gulf News, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…As the off shoots or whole palm trees in the first stages of infestation don't show any clear symptoms, the transport of this plant material with larvae and pupae of the RPW explains the notable invasiveness of this species. Furthermore the images were shown to disperse quite well, as mark-release-recapture studies revealed that these insects can move about 7 km in less than week (Abbas et al, 2006). While dispersing they seem to be attracted by 'ferrugineol' (4-methyl-5-nonanol), an aggregation pheromone that especially has an effect on females, which are twice as attracted as males (Hallett et al, 1993;Faleiro, 2009).…”
Section: Life Cyclementioning
confidence: 99%
“…Many previous studies have also reported female biased sex ratios in the pheromone trap catches Faleiro and Rangnekar, 2000;Vidyasagar et al, 2000a;Al-Saoud, 2011;Faleiro and Satarkar, 2003a;Soroker et al, 2005, Avalos andSoto, 2015). Although, a few studies (Hallett et al, 1993a;Muralidharan et al, 1999;Abbas et al, 2006) have reported no significant difference between male and female trap catches. In fact, if the trap catches are female biased, it is a significantly advantageous because each female adult captured counts towards reducing population buildup and preventing spread of infestation as most female adults recovered from pheromone traps have been reported to be young and gravid (Abraham et al, 2001;Faleiro et al, 2003).…”
Section: Yeast and Ethyl Acetatementioning
confidence: 99%
“…During or after devouring the host, adults emerge and fly out in search of food resources and mates and cause re-infestations or newly infest the healthy palms (Nirula, 1956;Estaban-Durán et al, 1998). These outbound adults are targeted by semiochemical-based trapping methods which have been used as the mainstay of IPM programs in many countries to monitor and mass-trap the RPW populations in the field (Oehlschlager et al, 1993;Abraham et al, 1998;Rajapakse et al, 1998;Vidyasagar and Subaharan, 2000;Vidyasagar et al, 2000b;Oehlschlager et al, 2002;Soroker et al, 2005;Abbas et al, 2006;El-Sayed et al, 2006). A major advantage of RPW pheromone trapping is that it attracts nearly twice the number of females than males and thereby further helping to reduce progenies (Oehlschlager, 1998;Vidyasagar et al, 2000b;Abraham et al, 2001;Faleiro et al, 2002;Faleiro, 2005;Jayanth et al, 2007;Vacas et al, 2013Vacas et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%